2017
DOI: 10.5888/pcd14.160573
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Body Mass Index: Are Weight-loss Programs the Best Way to Improve the Health of African American Women?

Abstract: African American women have higher prevalence (82%) of overweight (body mass index [BMI] 25–29) and obesity (BMI ≥30) than white women (63.2%) or Hispanic women (77.2%), and weight-loss programs yield minimal results in this population. We examine the concept of BMI as a measure of health for African American women and suggests a more holistic, multifaceted approach to preventing chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Obesity is one risk factor for development and potentiation of dyslipidemia. African American women have a higher prevalence of being overweight or obese (BMI ≥25) than white women (82.0 vs. 63.2%, respectively) ( Dodgen & Spence-Almaguer, 2017 ). Overweight and obese patients have increased risk of developing long-term health consequences, such as dyslipidemia, hypertension, diabetes, obstructive sleep apnea, and heart disease ( Bland & Sharma, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is one risk factor for development and potentiation of dyslipidemia. African American women have a higher prevalence of being overweight or obese (BMI ≥25) than white women (82.0 vs. 63.2%, respectively) ( Dodgen & Spence-Almaguer, 2017 ). Overweight and obese patients have increased risk of developing long-term health consequences, such as dyslipidemia, hypertension, diabetes, obstructive sleep apnea, and heart disease ( Bland & Sharma, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Cheng et al examining diabetes in the United States from 2011–2016, the prevalence of diabetes in African Americans was 20.4% compared to non-Hispanic Caucasians at 12.1% ( Cheng et al, 2019 ). African American women were also 1.9 times more likely to develop diabetes, 2.3 times as likely to develop end-stage renal disease, and 2.4 times more likely to die of diabetes complications when compared to white women ( Dodgen & Spence-Almaguer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…26 Therefore, using BMI reduces the complexities of the human body to 1 basic parameter. 27 Bioelectrical impedance analysis (BIA), one of the body composition measurement methods, provides detailed information, such as the mass and structure of tissues and organs, beyond that obtained from measuring height and weight. 24,25 With this method, the equipment sends out a weak electrical current to the upper or lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, both the Centers for Disease Control and Prevention (https://www.cdc.gov/pcd/issues/2017/16_0573.htm) and the National Institutes of Health (https://www.ncbi.nlm.nih.gov/pmc/articles/ PMC5477783/pdf/PCD-14-E48.pdf) publicized the article "Beyond Body Mass Index: Are Weight-Loss Programs the Best Way to Improve the Health of African American Women?" (Dodgen & Spence-Almaguer, 2017). The article indicated that African American women tend to lose even less weight than White women during dieting programs, followed by weight regain.…”
Section: Prestigious Journals Have Emphasized Lack Of Efficacy Of Wei...mentioning
confidence: 99%